Immunohistochemical analysis of NaPi2b protein (MX35 antigen) expression and subcellular localization in human normal and cancer tissues - Kiyamova, R.; Shyian, M.; Lyzogubov, V.V.; Usenko, V.S.; Gout, T.; Filonenko, V. (Experimental Oncology, 2011)
Aim: To study the expression profile of the NaPi2b protein and its localization in breast, ovarian and lung cancer cells in relation to normal tissues adjacent to tumor. Methods: Immunohistochemical analysis with monoclonal antibody MX35 was applied for investigation of NaPi2b protein expression in breast, lung and ovarian carcinomas. Intensity of NaPi2b protein expression was calculated with semiquantitative scores. Results: NaPi2b (MX35) protein expression was detected in breast, lung and ovarian cancer cells and adjacent normal tissue. We have shown that in contrast to ovarian tumors in breast and lung tumors NaPi2b expression is down regulated comparing to correspondent normal tissues. Conclusion: This study provides the data on the pattern of NaPi2b expression and cellular localization in breast, lung and ovarian cancers, which might be useful for understanding the mechanism of transport and maintenance of inorganic phosphate in cancer and normal cells, as well as for developing novel immunotherapeutic approaches based on MX35 monoclonal antibody.